Insights into Acinetobacter baumannii protective immunity - Sean Jeffreys; James P. Chambers; Jieh-Juen Yu; Chiung-Yu Hung; Thomas Forsthuber; Bernard P. Arulanandam; Bernard P. Arulanandam (Frontiers in Immunology, 2022)
Acinetobacter baumannii is a nosocomic opportunistic Gram-negative bacteria known for its extensive drug-resistant phenotype. A. baumannii hospital-acquired infections are major contributors to increased costs and mortality observed during the COVID-19 pandemic. With few effective antimicrobials available for treatment of this pathogen, immune-based therapy becomes an attractive strategy to combat multi-drug resistant Acinetobacter infection. Immunotherapeutics is a field of growing interest with advances in vaccines and monoclonal antibodies providing insight into the protective immune response required to successfully combat this pathogen. This review focuses on current knowledge describing the adaptive immune response to A. baumannii, the importance of antibody-mediated protection, developments in cell-mediated protection, and their respective therapeutic application going forward. With A. baumannii’s increasing resistance to most current antimicrobials, elucidating an effective host adaptive immune response is paramount in the guidance of future immunotherapeutic development.